Generational Differences as a Moderator of Relationships Between Transformational Leadership Style, Organizational Commitment, and Organizational Citizenship Behavior - Hindiarto, Ferdinand; Widjaja, Synthia Christin; Susetyo, Daniel Purwoko Budi (Gadjah Mada Journal of Psychology (GamaJoP), 2026)
Today, three generations (Gen X, Y, Z) work together in various organizations, making it a challenge forleaders to manage cross-generational employees. In addition, previous studies have found low levels of organizationalcommitment and organizational citizenship behavior (OCB) among Gen Y and Z employees. This study aimed to explain howgenerational differences moderate the relationships between transformational leadership style, organizationalcommitment, and OCB. The participants in this study were 216 employees in Semarang who belonged to Gen X, Y, and Z.Participants were recruited using convenience sampling. Data were analyzed using multigroup moderation on AMOS. Theresults showed that generational difference moderates the influence of transformational leadership style onorganizational commitment and OCB. The strongest generational influences on organizational commitment and OCB wereobserved in Gen Z.